A Lifecycle Analysis of a Floating Power Plant Using Biomethane as a Drop-In Fuel for Cold Ironing of Vessels at Anchorage - George Mallouppas; Angelos Ktoris; Elias Ar. Yfantis; Sotiris Petrakides; Marios Drousiotis (Energies)
The purpose of this research article is to perform a greenhouse gas (GHG) impact assessment using a lifecycle analysis of a cold-ironing solution for vessels at anchorage in a retrofitted barge and a marine genset combusting biomethane in dual fuel mode. A lifecycle methodology is developed based on the 4th International Maritime Organization (IMO) GHG study. Eleven impact scenarios are evaluated in terms of CO2 and harmful pollutants (SOx, CO, PM10, PM2.5, NMVOC, and NOx). Vessels operated by Petronav Ship Management Ltd are examined, specifically M/T Alexandria and M/T Astraia. The scenarios reveal CO2 reductions of up to 21% and CO increases of up to 60% due to the combustion of biomethane in dual fuel mode, alongside SOx reductions of up to 20% with increasing biomethane energy substitution. Particulates and NOx decrease due to the utilization of biomethane. This article presents a pragmatic solution for cold ironing for vessels at anchorage with proven lower GHG emissions with the exception of increased CO emissions, therefore the benefits outweigh the drawbacks.